Commercial bank loan and investment behaviour - Wood, John H. (London ; New York : Wiley, 1975)
In this series the authors attempts to give an account of the best econometric techniques available in the context of some set of applied problems.
Includes index.
Includes bibliographical references: p. 141-145.
rpm 08/05/2018
Loans
Keywords: Bank loans; Bank investments; Monetary policy